MANAJEMEN PEMBELAJARAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PADA SEKOLAH SMP IT AD DURRAH MEDAN MARELAN - Marpaung, Syafri Fadillah (Hijri, 2022)
The learning process requires a good management process in it.Therefore, every teacher before carrying out learning needs to carry out a good planning process in it both with online learning methods and offline learning. The instructor plays a crucial part in determining the amount and quality of learning that occurs. To increase the precision of learning for their pupils and enhance the caliber of instruction, teachers must carefully consider and prepare lesson plans. Due to the fact that the instructor manages learning, facilitates learning, provides excellent learning materials, and enhances students' listening skills, they are better able to grasp learning objectives and receive a high-quality education. Since there are multiple learning techniques used in the learning management process, including offline and online learning methods, the teacher must be able to master all of these learning methods at this time.Keywords: Administration, Quality, Education